Role of Cooperative Banks in Catering to the Credit Needs of Rural Masses - K. B., Nidheesh (Indian Journal of Marketing, 2009)
The study exams the impact of the co-operative banks for rural development. Data for the study were obtained from personal discussion through questionnaire. Result obtained from the study showed that the co-operative banks played a major role for the development of rural area in Kerala. Researcher made suggestion for improving the operational efficiency of rural banks in Kerala.